Early Detection of Mental Disorders and Psychosocial Problems in Students Taking Online Learning during COVID-19 Pandemic - Sirli Mardianna Trishinta; Wahidyanti Rahayu Hastutiningtyas; Yanti Rosdiana (Journal of Ners and Midwifery, 2022)
The online problems impact from online learning faced by students if not handled immediately will lead to the impact of mental disorders and psychosocial problems that are bigger and more serious. The aim of this study is to conducted early detection of mental disorders and psychosocial problems in nursing students who run online clinical practices during the COVID-19 pandemic at Tribhuwana Tunggadewi University, Malang. This research uses descriptive research with a cross-sectional study approach. That is, data between the independent and dependent variables collected at the same time. The population in this study were all students at Tribhuwana Tunggadewi University Malang, class of 2016, as many as 276 people. Sampling in this study is the total sampling technique is the overall sampling technique. This research used Chi square analytics to test the hypothesis. Result of this study shows that gender is significantly associated with psychological problems (p = 0.038), while gender has no relationship with the use of psychoactive use (p = 0.789), and PTSD (p = 0.551). It is concluded that mental disorders and psychosocial problems (i.e., psychological problem, psychoactive use, PTSD and unidentified psychologicaly) were prevalent among nursing students who run online clinical practice at Tribhuwana Tunggadewi. Students’ gender are associated with psychological problems, while has no associated with psychoactive use and PTSD. This study recommend that faculty authority, health professionals, and other professional related to mental health should play an important role for the prevention and earlier recognition of and intervention for psychosocial problems in nursing students who run online clinical practice during the COVID-19 pandemic.